Autonomous state security - Abdulkareem ِِAli; AbdulMenam, Feras (Journal of Legal Sciences, 2022)
The state, as one of the most important social institutions that works to provide services and security for individuals, needs security, and this security is achieved according to a specific hierarchy that starts from the security of the individual and the security of society to the security of the state, as the advanced state security is based on the basic pillars of solidarity and social peace This security consists of several levels (human, regional, social, economic, and cyber), unlike Arab criminal legislation, including Iraqi law, which is based on the concept of traditional state security, as it relies on the military side only in order to provide maximum criminal protection for the security of the political system The security of the government, and this was the result of the ideological influence of the authoritarian political regime on the criminal law before 2003, which aimed to reduce the security of the state to the security of the political system and the security of the government. After 2003, the political system shifted from an authoritarian regime to a democratic one, but this transformation did not remove the deliberate confusion between crimes against the security of the state and crimes against the security of the political system and the government, although crimes against the security of the state are distinguished from crimes against the security of the system.